Diarology for beginners: articulating playful practice through artless methodology. Issue 1 (2nd January 2020) - Munro, Kim; Murray, Peta; Taylor, Stayci
ABSTRACT: Here we set out to map, through epitextual moves, the first year of our practice-based research into 'diary performance', taking up Watkins and Krauth's call for 'new ways of "doing" and of "writing up" research that are discipline and form/genre relevant' (2016. "Radicalising the Scholarly Paper: New Forms for the Traditional Journal Article." TEXT: Journal of Writing and Writing Courses 20 (1) ). We offer the emergent methodology we call diarology much as it was discovered: chronologically, playfully and intuitively, through voicings, listenings, space for awkward silences and the serendipitous, and increasing attention to the métissage of our interleavings. We draw on the possibilities of playful practices both as means of inquiry and as sources of new knowledge, recalling Halberstam who encourages scepticism around modes of 'disciplinary correctness', suggesting they confirm the 'already known according to approved methods of knowing [but] do not allow for visionary insights of flight or fancy' (2011. The Queer Art of Failure . Durham: Duke University Press). The outcome re-purposes found materials to create new life narratives, each iteration finding form and gathering vitality within the extemporaneous/ephemeral architecture of 'essayesque dismemoir' (Murray 2017. "Essayesque Dismemoir: w/rites of elder-flowering". PhD Thesis, RMIT University).